Knowledge of Ribeirão Preto People Concerning Some Features About AIDS - Moriya, Tokico Murakawa; Gir, Elucir; Machado, Alcyone A.; Duarte, Geraldo; Oliveira, Maria Helena Pessini de (Brazilian Journal of Sexually Transmitted Diseases, 1996)
This investigation was carried out from a city of the interior of the state os São Paulo - Brazil. That has the fifth lúghest number of cases of AIDS registered in tlús country. Toe purpose of it was to investigate the knowledge on AIDS concerning its etiology, transmission ways, prevention and perception about the disease and the sick person. Toe data were collected in public squares where 600 people (0,13% of the total population of the city, male and fcmale, over 13 years old) were interviewed. Toe results revealed that a reduced number of persons have concepts completely correct and that there are some that do not know them or know them incorrcctly. Toe evidence that the population in general has isolated notions about AIDS make us recognize the necd of an ample programme of actions integratcd with the community. Toe health profcssional workers havc to assusme the leaderslúp in promoting educative actions among them, to the patients and to the public in general. Each one must be responsible to be well informed and to act against the actions that can affect lús own health and the health of others.